PENGARUH IKLAN DAN SERTIFIKASI PRODUK HALAL TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH - Riska Amalia; Ahmad Adib Nasution; Syamsul Effendi (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
The purpose of this study was to determine the effect of advertising (X1), Halal Certification (X2) on purchasing decisions (Y) with a population of 578 people. From this population, a sample of 100 people was taken from the students of the Faculty of Islamic Religion at the Islamic University of North Sumatra. This type of research is descriptive quantitative where the relationship of variables to the object under study is more cause and effect, so that in this research there are independent variables and dependent variables. As for the independent variable in this study is Advertising and Halal Certificate, while the dependent variable is Wardah Cosmetics Purchase Decision. The technique used for data collection is to use a questionnaire given to each respondent. The data is processed using SPSS version 22.0 for windows. The data analysis technique used is Multiple Linear Regression, with the formula Y = a + b1X1 +b2X2 + e. To find out the effect of advertising and Halal Certification on Wardah Cosmetics purchasing decisions, a comparison technique is used tcount with ttable equal to tcount ttable thus Ha is accepted because tcount ttable. From the results of the validity test and questionnaire reliability test, each statement item is declared valid and reliable if rcount is greater than rtable with Cronbach's Alpha value 0.60. And obtained the Regression equation Y = 6.984 + 0.432 X1 + 0.366 X2 + e, meaning that every 1% increase in Halal Advertising and Certification will cause an increase in purchasing decisions by 0.432 %. While the value of the determinant coefficient (r2) was obtained at 0.702 or 70.2%. Therefore, it can be concluded that Halal Advertising and Certification or the independent variables have a significant effect on the decision to purchase Wardah Cosmetics or the Bound Variable for Students of the Faculty of Islamic Religion at the Islamic University of North Sumatra. by 70.2%.